Synthesis, linear and nonlinear optical properties of thermally stable ferrocene-diketopyrrolopyrrole dyads. Issue 103 (6th October 2015) - Kaur, Sarbjeet; Dhoun, Sugandha; Depotter, Griet; Kaur, Paramjit; Clays, Koen; Singh, Kamaljit
Abstract : Thermally stable ferrocene-DPP dyads exhibit non-zero dipole moments as well as negative solvatochromism and show structure dependent second-order nonlinear polarizabilities. Abstract : A set of new ferrocene-diketopyrrolopyrrole (Fc-DPP) conjugated dyads was synthesized and their optical, nonlinear optical (NLO) and electrochemical properties were investigated. The second-order nonlinear polarizabilities were determined using hyper-Rayleigh scattering with femtosecond pulsed laser light at 840 nm. The dyads exhibited structure dependent NLO response, which could be explained by correlating optical as well as electrochemical data. In the latter case, it is shown that the amplitude of the Fc based one-electron redox process of D–π–A type dyads is doubled in the dyads of the type D–π–A–π–D, where the acceptor (DPP) is flanked by two Fc donors.